Beginner Election Training For Persons With Disabilities B (Speech Impaired) Using The E-Vote Flip Chart Method At The Banyuwangi State SLB Dormitory - Adawiyah, Putri Robiatul; Jatmiko, Hadi (Journal Of Humanities Community Empowerment, 2024)
This Community Service Training for Beginner Elections for Persons with Disabilities B (Deaf and Speech Impaired) Using the E-Vote Flip Chart Method in the Banyuwangi State SLB Dormitory, aims to overcome the problem of disability B in an effort to increase knowledge of Beginner Elections for the deaf and speech impaired (1) Minimal knowledge of voters for beginners with disabilities B (2) Minimal understanding of how to participate in elections (3) Lack of media tools that make it easier for deaf and speech impaired people to carry out elections (4) Minimal access to information and socialization media specifically for deaf and speech impaired in terms of elections for beginners. The solution is to hold training and simulations for beginner voters, including (1) providing knowledge to people with disabilities B regarding beginner elections (2) socialization of beginner elections for the deaf and speech impaired; (3) collaborating with partners in compiling the E-Vote Flip Chart; (4) inviting experts and related agencies with authority to socialize new voters, namely the Banyuwangi KPUD. (5) create a beginner election module; (6) Create an E-Vote Flip Chart. The output targets that have been achieved are increased understanding of training participants, online media publications, compiling service reports, articles related to service in the form of national journals or national proceedings, video and photo documentation of activities, E-Vote Flip Chart